Answer: ![4\sqrt{3}](https://tex.z-dn.net/?f=4%5Csqrt%7B3%7D)
Step-by-step explanation:
For this exercise it is important to remember the following:
![i=\sqrt{-1} \\\\i^2=-1](https://tex.z-dn.net/?f=i%3D%5Csqrt%7B-1%7D%20%5C%5C%5C%5Ci%5E2%3D-1)
Given the following expression:
![-2i\sqrt{-12}](https://tex.z-dn.net/?f=-2i%5Csqrt%7B-12%7D)
You can notice that the radicand (the number inside the square root) is negative. Therefore, in order to simplify the expression, you need to follow these steps:
1. Replace
with
and simplify:
![(-2i)(i)\sqrt{12}=-2i^2\sqrt{12}=-2(-1)\sqrt{12}=2\sqrt{12}](https://tex.z-dn.net/?f=%28-2i%29%28i%29%5Csqrt%7B12%7D%3D-2i%5E2%5Csqrt%7B12%7D%3D-2%28-1%29%5Csqrt%7B12%7D%3D2%5Csqrt%7B12%7D)
2. Descompose 12 into its prime factors:
![12=2*2*3=2^2*3](https://tex.z-dn.net/?f=12%3D2%2A2%2A3%3D2%5E2%2A3)
3. Substitute into the expression:
![=2\sqrt{2^2*3}](https://tex.z-dn.net/?f=%3D2%5Csqrt%7B2%5E2%2A3%7D)
4. Since
, you can simplify it:
![=(2)(2)\sqrt{3}=4\sqrt{3}](https://tex.z-dn.net/?f=%3D%282%29%282%29%5Csqrt%7B3%7D%3D4%5Csqrt%7B3%7D)
Answer: 22
Step-by-step explanation:
Since U is the midpoint of P and R, and S is the midpoint of P and Q, SU must be a midsegment.
By the midsegment theorem, SU is 1/2 the value of QR. Therefore QW = SU*2 = 11*2 = 22.
Answer:
57.72 in^2
Step-by-step explanation:
Question 1. Shapes are triangle, semi-circle, and rectangle.
Question 2.Find area of rectangle first. Then area of triangle and circle. Subtract area of triangle and circle. Then add the difference with the rectangles area.
Question 3.
Rectangle's area:<u>48 in^2</u>
Triangles area:8*4/2= <u>16 in^2</u>
Circle Area: pi*r^2/2(since its a semi-circle)
3.14*2^2=3.14*4=12.56/2=<u>6.28 in^2</u>
Question 4.
16-6.28=9.72
9.72+48=57.72 in^2
The answer is: x² – 6x + 9 = 0 .
_____________________________________________________
Explanation:
________________________________________________________
Given: (x – 3)² = 0 ; write as: general form: "ax² + bx + c = 0"; a ≠ 0 .
<span>
Note: </span>(x – 3)² = (x – 3)(x – 3) = x² – 3x – 3x + 9 = x² – 6x + 9 ;
___________________________________________________
Rewrite: (x – 3)² = 0 ; →
as: x² – 6x + 9 = 0 ; which is our answer.
____________________________________________
→ x² – 6x + 9 = 0 ; is in "general form", or "standard equation format"; that is: " ax² + bx + c = 0 "; (a ≠ 0) ;
→ in which:
a = 1 (implied coefficient, since anything multiplied by "1" is that same value);
b = -6;
c = 9
_______________________________________________________
Answer:
itd x=68 and y=5 I apolgize if its wrong